Middle Jurassic ooidal ironstones (southern Tibet): Formation processes and implications for the paleoceanography of eastern Neo-Tethys - Han, Kaibo; Han, Zhongpeng; Garzanti, Eduardo; Zhu, Shuaipeng; Yao, Hanwei; Guo, Huifang; Liu, Xuan; Wang, Chengshan (Frontiers in Earth Science, 2023)
All along the Tethyan Himalaya, a peculiar interval characterized by ooidal ironstones of Dingjie Formation (Ferruginous Oolite Formation, FOF) marks the base of the organic-rich Spiti Shale. This laterally-extensive ooidal ironstone interval is a fundamental testimony of the mechanisms that led to major paleoceanographic changes occurred in the eastern Neo-Tethys during the Middle Jurassic. Here we illustrate in detail the petrology, mineralogy, and geochemistry of ooidal ironstones and the major element contents of the entire Lanongla section. The FOF is characterized by significantly high contents of Fe2O3 (56.80%±9.07%, n=7) and P2O5 (1.72%±1.19%, n=7). In contrast, the Fe2O3 and P2O5 contents average 3.58% and 0.15% in the overlain carbonates of Lanongla Fm., and 5.55% and 0.16% in the overlying Spiti Shale. The ooidal ironstones are mainly composed of iron ooids with a few quartz grains and bioclasts cemented by sparry calcite. The iron ooids consist of concentric dark layers of francolite (carbonate fluorapatite), hence enriched in Ca, P and F, and bright layers of chamosite, enriched in Fe, Si, Al and Mg. Precipitation of francolite ensued from oversaturation of phosphorous ascribed to intensified upwelling, high biogenous productivity, and degradation of organic matter, whereas formation of chamosite reflects enhanced continental weathering and erosion leading to increased Fe input to the ocean during transgressive stages characterized by low sedimentation rate and scarce oxygenation at the sea floor. Modern upwelling zones in outer shelf or slope areas perform the similar geochemical characteristics to those as observed in this study. Fluctuating redox conditions induced the alternate growth of francolite under anoxic conditions and of chamosite under suboxic conditions. Ooids were thus formed on the sea-floor during continued resuspension and vertical oscillations of the chemocline rather than from interstitial waters after burial. The mineralogy of iron ooids indicates mainly reducing conditions in the water column, suggesting that extensive upwelling along the continental margin of eastern Neo-Tethys contributed significantly to the transition from carbonate deposits to organic-rich black shales during the Jurassic, as testified by the transition from well oxygenated in Lanongla Fm. to reduced condition in Spiti Shale indicated by the Mn/Al ratios compared to PAAS.